Love Canal: Reminder of Why We Celebrate Earth Day - Frederick W. Stoss; Carole Ann Fabian (Issues in Science and Technology Librarianship)
As we celebrate the 30th anniversary of Earth Day, it is fitting to take a look some of the reasons why a 30-something activist's movement still deserves our attention. This article describes the efforts of a small, Upstate New York community in dealing with the impacts of chemical wastes buried, almost literally, in the center of its neighborhood. Love Canal is remembered on Earth Day for two reasons. First, we remember Love Canal for where we have been for a substantial portion of Earth Day's thirty years. Second we remember Love Canal as an icon of work for the environment that still needs to be done. This article also tells how one library has handled an unexpected success story, to keep a temporary exhibit "alive."